PENGEMBANGAN KECAKAPAN HIDUP(LIFE SKILL) MELALUI PENANAMAN ETOS KERJA DAN MEMBANGUN KREATIVITAS ANAK - Siti Irene Astuti D (Jurnal Cakrawala Pendidikan, 2003)
The noncompetitive qualityof the Indonesian human resourcesis one proofof the educational world's failure to reach nationaleducational goals. Therefore, there needs to be arevolutionarymovement in the educational process of the nation's youngergeneration because the processofeducation continues to change anddevelop, suggesting various unpredictable future trends.The processof child education needs to be reordered, especiallythat for early child growth. Buildingup the spirit in anything byimplanting· work ethos and optimizing creativity development athome and at school areof utmost importance because both workethos and creativity are social assets that children need to developtheir various life skills.Life skills are broader in sense than skills for work because theyare at the other endof the continuum starting with the knowledgeand capability one needsto function independently in life. Bypossessing the life skills one will confidently face life and itsproblems withoutany feeling of extreme pressure, proactively andcreatively find solutionsto various problems in life, and becomemore successful in life